2022
DOI: 10.1186/s12876-022-02460-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison the effects and side effects of Covid-19 vaccination in patients with inflammatory bowel disease (IBD): a systematic scoping review

Abstract: Covid-19 is a pandemic disease that is more severe and mortal in people with immunodeficiency, such as those with inflammatory bowel disease (IBD). On the other hand, no definitive treatment has been identified for it and the best way to control it is wide spread vaccination. The aim of this study was to evaluate the benefits and side effects of different vaccines in patients with IBD. Three Electronic databases [Medline (accessed from PubMed), Scopus, Science Direct, and Cochrane] were searched systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It is noteworthy that there is evidence of lower vaccine uptake among patients undergoing steroid or biological therapy; our systematic review also elucidates the reasons behind this hesitancy, with patients expressing fears about vaccine effectiveness and the potential for severe side effects, such as exacerbation of the underlying disease [24][25][26][27]33]. Indeed, the safety profile of vaccination in individuals receiving immunosuppressive treatment is comparable to that in healthy subjects; similarly, while slightly reduced in immunocompromised individuals, the effectiveness remains sufficiently high to safeguard vulnerable patients [4,[13][14][15][16]. In particular, a multicenter Italian study conducted in 2022 interviewed 809 vaccinated IBD patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is noteworthy that there is evidence of lower vaccine uptake among patients undergoing steroid or biological therapy; our systematic review also elucidates the reasons behind this hesitancy, with patients expressing fears about vaccine effectiveness and the potential for severe side effects, such as exacerbation of the underlying disease [24][25][26][27]33]. Indeed, the safety profile of vaccination in individuals receiving immunosuppressive treatment is comparable to that in healthy subjects; similarly, while slightly reduced in immunocompromised individuals, the effectiveness remains sufficiently high to safeguard vulnerable patients [4,[13][14][15][16]. In particular, a multicenter Italian study conducted in 2022 interviewed 809 vaccinated IBD patients.…”
Section: Discussionmentioning
confidence: 94%
“…In light of the increased susceptibility to severe COVID-19, international gastroenterology scientific societies and public health institutions recommend COVID-19 vaccination for patients with IBD and immunocompromised individuals [11,12]. Although phase III trials for COVID-19 vaccines did not include IBD patients or those on immunosuppressive therapies, phase IV studies have shown that the vaccines are highly effective, immunogenic, and safe for this subgroup population [4,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, no worsening or flare-up of the disease following vaccination has been proved. Thus, vaccines are considered a safe and well-tolerated strategy for IBD patients[ 171 , 172 ].…”
Section: Liver Manifestations Associated With Covid-19mentioning
confidence: 99%